2013
DOI: 10.1088/0031-9155/58/22/8253
|View full text |Cite
|
Sign up to set email alerts
|

Automaticin vivoportal dosimetry of all treatments

Abstract: At our institution EPID (electronic portal imaging device) dosimetry is routinely applied to perform in vivo dose verification of all patient treatments with curative intent since January 2008. The major impediment of the method has been the amount of work required to produce and inspect the in vivo dosimetry reports (a time-consuming and labor-intensive process). In this paper we present an overview of the actions performed to implement an automated in vivo dosimetry solution clinically. We reimplemented the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 14 publications
1
49
0
2
Order By: Relevance
“…The largest clinical experience so far is the one carried out at Netherland NKI-AVL center where almost all curative patients irradiated with intensity-modulated techniques are nowadays verified by means of EPID-based IVD in their first three treatment fractions. The findings of this experience have been recently published by Olaciregui-Ruiz et al [22]; using a new automated IVD solution, the authors reported on average 18% of verified plans outside at least one of their tolerance levels.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…The largest clinical experience so far is the one carried out at Netherland NKI-AVL center where almost all curative patients irradiated with intensity-modulated techniques are nowadays verified by means of EPID-based IVD in their first three treatment fractions. The findings of this experience have been recently published by Olaciregui-Ruiz et al [22]; using a new automated IVD solution, the authors reported on average 18% of verified plans outside at least one of their tolerance levels.…”
Section: Introductionsupporting
confidence: 53%
“…In addition, following the approach of Olaciregui-Ruiz et al [22], future investigations will be addressed on the feasibility of implementing an automated analysis able to automatically run the IVD procedure.…”
Section: Discussionmentioning
confidence: 99%
“…It can hardly be applied indiscriminately to large cohorts of patients. Selecting which patients would really benefit from plan adaptation is not an obvious task because it can be dependent on treatment technique, evaluation method, anatomical site and even the patient . For lung, treatment plans are often assessed through weekly or daily CBCT imaging.…”
Section: Introductionmentioning
confidence: 99%
“…While not the most accurate dose verification tools, in vivo portal dosimetry nevertheless finds numerous clinical applications . Three‐dimensional dose evaluation has been successfully implemented through dose prediction or back‐projection of the EPID signal . While extremely promising, these methods can be labor‐intensive to implement, commission, and use.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 An EPID transit dosimetry model using the convolution approach was also widely published by researchers at the Netherlands Cancer Institute (NKI-AVL) where the model is now in clinical use. [12][13][14][15][16][17][18] Instead of using the convolution approach, an empirical method is more practical for the majority of clinical centres with limited resources for computationally intensive simulations or mathematical modelling. 2D transit dosimetry using an empirical method was first described by Evans et al 19 and Symonds-Tayler et al 20 for an in-house imaging panel and later by Evans et al 21 for a commercial scanning liquid-filled ionization chamber (SLIC) EPID.…”
mentioning
confidence: 99%